Land-Use and Transport: a Review and Discussion of Dutch Research - van Wee, Bert; Maat, Kees (European Journal of Transport and Infrastructure Research, 2003)
Numerous studies of the interaction between land use and transport have been carried out in the past. In this paper we evaluate a selection of Dutch studies. Before reviewing the studies, we present a conceptual model for passenger transport (section 2), give an overview of the way in which land-use influences travel behaviour (section 3). We also give an overview of transport in Dutch land-use policy plans (section 4) and a categorisation of research (section 5). We then review empirical studies (section 6) and model-simulation studies (section 7) of the impact of land-use on transport. This is followed by a synthesis of the results and look at the transferability of results to other countries (section 8), a discussion of the policy implications of our findings (section 9) and some suggestions for further research (section 10).